A transparent electrode based on polyacid treatment and its preparation method and application

The conductive properties of PEDOT:PSS film are improved by polyacid treatment, and the problems of poor performance improvement and dangerous reaction conditions in the prior art are solved, and efficient charge collection and hole transmission are achieved, and the process is simple, environmentally friendly and cost-effective.

CN113285032BActive Publication Date: 2025-04-18HUANENG RENEWABLES CORPORATION LIMITED +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202110546766.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-05-19
Publication Date
2025-04-18
Estimated Expiration
2041-05-19

AI Technical Summary

Technical Problem

In the prior art, the method of improving the conductive properties of PEDOT:PSS films has poor results and dangerous reaction conditions, which affects environmental friendliness and cost control.

Method used

The polyacid treatment method is adopted, including preparing a polyacid solution, preparing a PEDOT:PSS film by solution film forming method, and performing the first and second surface treatments, and using the polyacid solution to improve the conductive properties of the film.

Benefits of technology

It improves the conductivity of transparent electrodes, realizes efficient charge collection and hole transmission, and has a simple process, environmentally friendly and low cost, which is suitable for the large-scale preparation of perovskite solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113285032B_ABST
    Figure CN113285032B_ABST
Patent Text Reader

Abstract

The present invention discloses a transparent electrode based on polyacid treatment and its preparation method and application, which belongs to the field of perovskite solar cell components. A polyacid-treated PEDOT:PSS film is used as a transparent electrode layer and a hole transport layer, a PEDOT:PSS solution is selected as a precursor solution, and an existing solution processing method such as a uniform glue spin coating method, a wire rod coating method, a doctor blade coating method, a slit extrusion coating method, a screen printing method, a gravure printing method, a relief printing method, etc. can be used to prepare a high-performance transparent electrode, which can be used as a hole transport functional layer. The preparation process is simple, and the preparation process of the battery is simplified. The perovskite solar cell prepared according to the transparent electrode of the present invention has a higher charge collection efficiency and a lower charge loss at the electrode interface, and thus has a higher photoelectric conversion efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of perovskite solar cell components and relates to a transparent electrode based on polyacid treatment and a preparation method and application thereof. Background Art

[0002] Perovskite solar cells are a new type of organic / inorganic hybrid battery, and its basic structure includes transparent electrodes, hole transport layers, perovskite active layers, electron transport layers and metal electrode layers. The transparent electrode in perovskite cells generally refers to the functional layer with substrate materials, which can usually be divided into the following categories: 1. Doped metal oxide transparent electrodes, including ITO (Indium Tin Oxide), FTO (Fluorine-doped Tin Oxide), ATO (Aluminum-doped Tin Oxide) and AZO (Aluminum-doped Zinc Oxide), etc., and the processing technology is usually sputtering film formation; 2. Carbon material transparent electrodes, such as carbon nanotubes (CNT) and graphene (Graphene), the processing technology is to disperse them into solvents through high-power ultrasound or chemical modification and then process them into films through solution processing; 3. Metal nanowires, metal nanogrids and ultra-thin metal film transparent electrodes, the metal types include silver, copper, gold, etc., and the processing technology includes solution processing, thermal evaporation and sputtering processes; 4. Doped conductive polymers, the processing technology is usually solution processing film formation.

[0003] ITO transparent electrodes have limited long-term large-scale applications due to many factors, such as complex processing technology, high equipment cost, cost disadvantages caused by limited reserves of indium materials, and the brittleness of the materials themselves. 5 S / m), band gap can be easily adjusted by chemical synthesis, doping and other means, and can be processed in solution, which makes it have very unique advantages in transparent electrode applications. PEDOT is a conductive polymer material developed by Bayer in Germany in 1988 with simple molecular structure, small band gap, high conductivity and other characteristics. Subsequently, it was widely used in many fields such as organic thin film solar cells, organic light-emitting diodes, organic field effect transistors and electrochromic devices due to its high conductivity (>1000S / cm), good thermal stability in oxidation state, high transmittance (visible light transmittance ~95%, film thickness <30nm) and other advantages. On the other hand, in order to solve the problem of PEDOT's own insolubility that limits its application, water-soluble sodium polystyrene sulfonate (PSSA) was introduced. The introduction of PSSA realizes the solution processing of PEDOT and broadens its application field. However, the presence of PSS in the film also weakens the conductive properties of PEDOT.

[0004] In order to solve the problem of relatively weak conductivity of PEDOT:PSS film, it has been reported that the conductivity of the film is improved by adding surfactants and amphoteric compounds to the PEDOT:PSS aqueous solution, or by treating the surface of the PEDOT:PSS film with strong acid, strong base or salt compounds. Currently reported methods for improving conductivity, such as adding additives to the solution, have little effect on improving conductivity. Surface treatment methods such as strong acid and strong base treatment have relatively dangerous reaction conditions and are not very environmentally friendly. Summary of the invention

[0005] In order to overcome the shortcomings of the prior art in improving the conductivity of PEDOT:PSS thin films, such as low conductivity improvement effect and dangerous reaction conditions, the present invention aims to provide a transparent electrode based on polyacid treatment and a preparation method and application thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a transparent electrode based on polyacid treatment comprises the following steps:

[0008] Step 1) preparing a polyacid solution stock solution; the polyacid is any one of molybdic acid, phosphomolybdic acid, tungstic acid and phosphotungstic acid;

[0009] Step 2) Preparation of PEDOT:PSS thin film: PEDOT:PSS is prepared on a transparent substrate by a solution film forming method to obtain a PEDOT:PSS thin film, which is annealed for later use;

[0010] Step 3) first surface treatment: immersing the PEDOT:PSS film annealed in step 2) into a polyacid solution, followed by washing and annealing in sequence to obtain a transparent electrode precursor;

[0011] Step 4) Second surface treatment: a polyacid solution is dripped onto the surface of the transparent electrode precursor, and then excess polyacid solution is removed to obtain a transparent electrode based on polyacid treatment.

[0012] Preferably, in step 1), the solvent in the polyacid solution includes methanol, ethanol, ethylene glycol, isopropanol, or glycerol.

[0013] Preferably, in step 1), the concentration of the polyacid solution stock solution is 0.2-15 mg / ml.

[0014] Preferably, the transparent substrate is glass, PET material, PI material or PC material.

[0015] Preferably, in step 2), the thickness of the PEDOT:PSS film is 30-150 nm.

[0016] Preferably, in step 3), during the first surface treatment, the concentration of the polyacid solution used is 5 to 15 mg / ml;

[0017] In step 4), during the second surface treatment, the concentration of the polyacid solution used is 0.2-1 mg / ml.

[0018] Preferably, in step 3), the reaction conditions for the first surface treatment are: soaking at room temperature for 10 to 60 minutes;

[0019] In step 4), during the second surface treatment, the polyacid solution is dripped until it covers the surface of the film.

[0020] Preferably, in step 3), the specific operation of cleaning is: immersing the PEDOT:PSS film in a methanol or ethanol solution for rinsing for 1 to 3 minutes and then taking it out;

[0021] The specific operation of annealing is: annealing the rinsed PEDOT:PSS film at 100-150° C. for 10-60 minutes.

[0022] Preferably, in step 2), the solution film forming method is spin coating, wire rod coating, slot extrusion coating or printing method.

[0023] In step 4), excess polyacid solution is removed, specifically by spin coating, doctor blade coating or slit coating.

[0024] A transparent electrode based on polyacid treatment is obtained according to the preparation method of the transparent electrode based on polyacid treatment, wherein the thickness of the transparent electrode based on polyacid treatment is 30 to 150 nm.

[0025] A polyacid-treated transparent electrode is used in the preparation of a perovskite solar cell. The structure of the perovskite solar cell includes, from bottom to top, a transparent electrode layer, a hole transport layer, a perovskite active layer, an electron transport layer and a metal electrode layer. The polyacid-treated transparent electrode serves as a transparent electrode layer and / or a hole transport layer.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The present invention provides a method for preparing a transparent electrode based on polyacid treatment, which has the advantages that the functional layer has high conductivity, which is beneficial to charge collection and hole transport; the performance of the functional layer film can be regulated by adjusting the film component ratio, and the preparation process is simple, environmentally friendly and low in cost.

[0028] The present invention also discloses a transparent electrode based on polyacid treatment, which is prepared based on the above method. The transparent electrode can replace the traditional ITO transparent electrode as a new transparent electrode, and has high conductivity and high transmittance in the visible light region. The polyacid-treated PEDOT:PSS film is used as the transparent electrode layer and the hole transport layer, and the PEDOT:PSS solution is selected as the precursor solution. The existing solution processing methods such as uniform glue spin coating, wire rod coating, blade coating, slit extrusion coating, screen printing, gravure printing, relief printing, etc. can be used to prepare a high-performance transparent electrode, which can be used as a hole transport functional layer. The preparation process is simple, and the preparation process of the battery is simplified. The perovskite solar cell prepared according to the transparent electrode of the present invention has a high charge collection efficiency and a low charge loss at the electrode interface, and thus has a high photoelectric conversion efficiency.

[0029] Furthermore, polyacid surface treatment can also optimize the work function of PEDOT:PSS films. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the basic structure diagram of a perovskite solar cell;

[0031] Figure 2 Schematic diagram of the structure of a perovskite solar cell without a hole transport layer;

[0032] Figure 3 Schematic diagram of the molecular structure of the compound; wherein (a) is the molecular structure of PEDOT:PSS; (b) is the molecular structure of PTAA;

[0033] Figure 4 The transmittance spectra of different types of transparent electrodes in the 350-900nm band;

[0034] Figure 5 This is a current density-voltage relationship curve of the perovskite solar cell prepared in the example.

[0035] Among them: 1-transparent electrode layer; 2-hole transport layer; 3-perovskite active layer; 4-electron transport layer; 5-metal electrode layer. DETAILED DESCRIPTION

[0036] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0037] Embodiment 1 (reference example):

[0038] The preparation of perovskite solar cells based on ITO transparent electrodes includes the following steps:

[0039] Step 1) Take 2 mg of PTAA (molecular structure as Figure 3The precursor solution of the hole transport layer was prepared by dissolving the precursor solution of the hole transport layer in 1 ml of toluene solvent under nitrogen atmosphere and stirring at room temperature overnight until the precursor solution was completely dissolved.

[0040] Step 2) The method for cleaning the patterned ITO glass is as follows: a) The glass is immersed in water with a surfactant such as detergent and ultrasonically treated (power 70W) for 10 minutes, twice; b) After rinsing with water until there is no foam, the glass is immersed in deionized water and ultrasonically treated (power 70W) for 10 minutes, twice; c) The glass is immersed in acetone and ultrasonically treated (power 70W) for 10 minutes, twice; d) The glass is immersed in anhydrous ethanol or isopropanol and ultrasonically treated (power 70W) for 10 minutes, twice. After UVO treatment for 15 minutes, move into a nitrogen-protected glove box for use;

[0041] Step 3) The PTAA hole transport layer precursor solution described in step (1) is spin-coated on the ITO glass obtained in step (2) at a spin-coating speed of 6000 rpm / min for 30 seconds, followed by annealing at 100°C for 30 minutes. The film thickness is about 30 nm, thereby obtaining a hole transport layer 2.

[0042] Step 4) 1290.8 mg PbI2 and 445.2 mg MAI were dissolved in a mixed solvent of DMF and DMSO (the volume ratio of DMF and DMSO was 4:1), and stirred at room temperature overnight to obtain a perovskite precursor solution, in which the total solute concentration in the solution was 1.4 mol / ml.

[0043] Step 5) Take 12.5 mg PC 61 BM was dissolved in 1 ml of toluene solvent and stirred at room temperature overnight to obtain an electron transport layer precursor solution with a solution concentration of 12.5 mg / ml.

[0044] Step 6) Spin coating the perovskite precursor solution of step (3) on the hole transport layer 2 obtained in step (3): the whole spin coating process is divided into three steps, first, spin coating at 4000 rpm / min for 3 seconds; then spin coating at 5000 rpm / min for 30 seconds; finally, add 200 μl of chlorobenzene (anti-solvent) at 5000 rpm / min for 11 seconds, and the requirement is that all the anti-solvent is added within 2 seconds. The thickness of the perovskite active layer 3 is controlled to be about 500 nm.

[0045] Step 7) The wafer obtained in step (6) was annealed at 75°C for 2 minutes in a nitrogen atmosphere and then heated to 90°C for 4 minutes.

[0046] Step 8) Spin-coat the PC obtained in step (4) on the wafer obtained in step (7) 61 For BM solution, the spin coating steps were 4000 rpm / min for 3 seconds and 5000 rpm / min for 30 seconds, and the film thickness was about 20 nm.

[0047] Step 9) The wafer obtained in step (8) is moved into a vacuum deposition chamber and evacuated to a vacuum degree of less than 4*10 -4 After Pa, the electron transport layer 4 was prepared by thermal evaporation deposition method; C 60 The evaporation rate is less than 0.05 angstroms / second, and the film thickness is 20nm; the BCP evaporation rate is less than 0.1 angstroms / second, and the film thickness is 9nm.

[0048] Step 10) The sheet obtained in step (9) is also prepared by thermal evaporation deposition method to prepare silver electrode as metal electrode layer 5, and the vacuum degree is controlled to be less than 4*10 -4 Pa, evaporation rate 1-2 angstroms / second, silver electrode thickness 100nm, and a perovskite battery device was prepared.

[0049] Example 2

[0050] The perovskite solar cell based on the PEDOT:PSS film treated with molybdate once as a transparent electrode is prepared as follows: Figure 1 shown.

[0051] Step 1) PH1000 is selected as the precursor solution of PEDOT:PSS transparent electrode.

[0052] Step 2) The solution of step (1) is added dropwise onto the cleaned and UVO treated glass substrate, and a transparent electrode layer 1 is prepared by spin coating at a speed of 2000 rpm / min and a film thickness of about 50 nm. The film is then annealed at 120° C. in air for 30 minutes and then used for later use.

[0053] Step 3) 25 mg of molybdic acid was dissolved in 50 ml of methanol solvent and stirred at room temperature until completely dissolved (clear and transparent solution) to obtain a molybdic acid solution for the first surface treatment, with a solution concentration of 0.5 mg / ml.

[0054] Step 4) The transparent electrode layer 1 obtained in step (2) is immersed in the molybdic acid solution of step (3) for 30 minutes.

[0055] Step 5) After the immersion in step (4), the transparent electrode layer 1 is rinsed with anhydrous methanol solvent for 2-3 times, then annealed at 120° C. for 30 minutes and moved into a nitrogen-protected glove box for standby use. The PEDOT:PSS film after one treatment is used as the transparent electrode layer 1 of the perovskite solar cell.

[0056] The preparation of other functional layers such as the hole transport layer 2 , the perovskite active layer 3 , the electron transport layer 4 and the metal electrode layer 5 is the same as in Example 1.

[0057] Example 3

[0058] Preparation of perovskite solar cells with PEDOT:PSS film as transparent electrode layer based on one-time treatment (treatment with molybdenum acid solution of different concentrations)

[0059] Except that the concentration of the molybdic acid solution was changed to 1 mg / ml, all steps were the same as in Example 2.

[0060] Example 4

[0061] Preparation of perovskite solar cells with PEDOT:PSS film as transparent electrode layer based on one-time treatment (treatment with molybdenum acid solution of different concentrations)

[0062] All steps were the same as in Example 2 except that the concentration of the molybdic acid solution was changed to 2 mg / ml.

[0063] Example 5

[0064] Preparation of perovskite solar cells with PEDOT:PSS film as transparent electrode layer based on one-time treatment (treatment with molybdenum acid solution of different concentrations)

[0065] Except that the concentration of the molybdic acid solution was changed to 5 mg / ml, all steps were the same as in Example 2.

[0066] Example 6

[0067] Preparation of perovskite solar cells based on PEDOT:PSS thin film as transparent electrode treated with one treatment (molybdate solution with different concentrations)

[0068] All steps were the same as in Example 2 except that the concentration of the molybdic acid solution was changed to 10 mg / ml.

[0069] Example 7

[0070] Preparation of perovskite solar cells based on double-processed PEDOT:PSS film as transparent electrode layer

[0071] (1) Preparation of precursor solution for secondary treatment with molybdic acid solution: In a nitrogen-protected glove box, 0.5 mg of molybdic acid was dissolved in 1 ml of methanol solvent and stirred at room temperature until completely dissolved (clear and transparent solution) to obtain a molybdic acid solution for the second surface treatment, with a solution concentration of 0.5 mg / ml.

[0072] (2) The molybdate solution of relatively low concentration obtained in step (6) is added dropwise to the surface of the transparent electrode after the first treatment obtained in Example 3, and the molybdate solution of relatively low concentration is spin-coated by a uniform coating method. The spin-coating speed is 3000 rpm / min and the spin-coating time is 30 seconds. The treated transparent electrode does not need to be treated and directly proceeds to the next step.

[0073] The preparation of other functional layers such as the perovskite active layer 3, the electron transport layer 4 and the metal electrode layer 5 is the same as described in Example 1.

[0074] Example 8

[0075] Preparation of perovskite solar cells based on PEDOT:PSS film treated with phosphomolybdic acid once as transparent electrode layer

[0076] Except that molybdic acid solution is replaced with phosphomolybdic acid solution of same concentration (solution concentration is 1mg / ml), other steps are with embodiment 3.

[0077] Example 9

[0078] Preparation of perovskite solar cells based on PEDOT:PSS film treated with phosphomolybdic acid as transparent electrode layer

[0079] Except that molybdic acid solution is replaced with phosphomolybdic acid solution of same concentration (surface treatment phosphomolybdic acid solution concentration is 1mg / ml for the first time, and surface treatment phosphomolybdic acid solution concentration is 0.5ml / ml for the second time), other steps are with Example 7.

[0080] Example 10

[0081] Preparation of perovskite cells based on PEDOT:PSS film treated with tungstic acid as transparent electrode layer 1 and hole transport layer 2

[0082] Except that the molybdic acid solution is replaced with a tungstic acid solution of the same concentration (the concentration of the phosphomolybdic acid solution for the first surface treatment is 1 mg / ml, and the concentration of the phosphomolybdic acid solution for the second surface treatment is 0.5 ml / ml), the other steps are the same as those in Example 7.

[0083] Embodiment 11

[0084] The perovskite cell was prepared based on the secondary treatment of PEDOT:PSS film with phosphotungstic acid as the transparent electrode layer 1 and the hole transport layer 2, and the structure was as follows Figure 2 shown.

[0085] Except that the molybdic acid solution is replaced with a phosphotungstic acid solution of the same concentration (the concentration of the phosphomolybdic acid solution for the first surface treatment is 1 mg / ml, and the concentration of the phosphomolybdic acid solution for the second surface treatment is 0.5 ml / ml), the other steps are the same as in Example 7.

[0086] It should be noted that the molecular structures of PEDOT:PSS and PTAA used in the examples are as follows: Figure 3As shown. The ITO glass cleaning method is as follows: a) The glass is immersed in water with added surfactants such as detergent and ultrasonically applied (power 20-70W) for 10-15 minutes, twice; b) After rinsing with water until there is no foam, the glass is immersed in deionized water and ultrasonically applied (power 20-70W) for 10-15 minutes, twice; c) The glass is immersed in acetone and ultrasonically applied (power 20-70W) for 10-15 minutes, twice; d) The glass is immersed in anhydrous ethanol or isopropanol and ultrasonically applied (power 20-70W) for 10-15 minutes, twice. After UVO treatment for 15 minutes, it is moved into a nitrogen-protected glove box for standby use. The transparent substrate can be made of glass, PET, PI or PC materials; the solution film forming methods include spin coating, wire rod coating, slit extrusion coating, printing and other methods.

[0087] The transmittance of the ITO transparent electrode and the transparent electrodes prepared in Examples 2 to 11 was tested in the visible light region. The results are as follows: Figure 4 shown.

[0088] The test results show that the light transmittance of the pure PH1000 film in the long-wave region above 550nm is significantly lower than that of the ITO film, while the light transmittance of the transparent electrode (Example 2, Example 3, Example 4, Example 5, Example 6, Example 8) treated once with molybdic acid or phosphomolybdic acid in this region (550-900nm) is significantly improved. Among them, there is a preferred concentration range for the treatment of the transparent electrode in the polyacid solution. When the transparent electrode is treated twice, the test results clearly prove that the light transmittance of molybdic acid, tungstic acid, phosphomolybdic acid and phosphotungstic acid in the entire test area (350-900nm) is significantly better than that of the ITO transparent electrode, and the average light transmittance is greater than 85%. Among them, the light transmittance of phosphomolybdic acid and phosphotungstic acid is greater than 90%. In summary, the results show that the new transparent electrode provided by the present invention is superior to the widely used ITO transparent electrode in terms of light transmittance in the visible light region.

[0089] The photoelectric performance test of the battery prepared in the above embodiment is carried out:

[0090] The cell was tested using a solar simulator (xenon lamp as light source) at a standard sunlight intensity (AM1.5G, 100mW / cm 2 ) was tested under the conditions of 100 ℃ and 100 ℃ respectively. The solar simulator was calibrated using a silicon diode (with a KG9 visible filter) at the National Renewable Energy Laboratory. The performance parameters of the tested cells are shown in Table 1. The current density-voltage curve is shown in Table 1. Figure 5 shown.

[0091] Table 1 Performance parameters of perovskite solar cells prepared according to different embodiments

[0092]

[0093]

[0094] The performance test data of perovskite solar cells prepared according to different embodiments show that: when a polyacid is used for a single treatment, considering the difference in HOMO energy level between the transparent electrode surface work function and the perovskite active layer, the open circuit voltage and short circuit current are both reduced compared to the reference cell; and the transparent electrode surface work function after the secondary treatment is optimized to a certain extent, so the open circuit voltage and fill factor are better than the reference cell, thereby showing a photoelectric conversion efficiency equivalent to or higher than that of the reference cell.

[0095] The above results prove that the new transparent electrode proposed in the present invention can be used as the transparent electrode layer and hole transport layer of the perovskite battery at the same time; the new transparent electrode provided by the present invention also has the advantage of being able to be solution processed at room temperature. In summary, the transparent electrode has the advantages of simple processing technology, easy large-scale preparation, environmental friendliness and low cost. The new transparent electrode provided by the present invention has great advantages in large-scale preparation of perovskite solar cells, process simplification, cost control and flexible device preparation.

[0096] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a transparent electrode based on polyacid treatment, characterized in that: The steps include: Step 1) preparing a polyacid solution stock solution; the polyacid is any one of molybdic acid, phosphomolybdic acid, tungstic acid and phosphotungstic acid; Step 2) Preparation of PEDOT:PSS thin film: PEDOT:PSS is prepared on a transparent substrate by a solution film forming method to obtain a PEDOT:PSS thin film, which is annealed for later use; Step 3) First surface treatment: soaking the PEDOT:PSS film annealed in step 2) in a polyacid solution, followed by washing and annealing in sequence to obtain a transparent electrode precursor; Step 4) Second surface treatment: adding a polyacid solution to the surface of the transparent electrode precursor, and then removing excess polyacid solution to obtain a transparent electrode based on polyacid treatment; In step 1), the solvent in the polyacid solution includes methanol, ethanol, ethylene glycol, isopropanol, or glycerol; PEDOT:PSS is PH4083 or PH1000; In step 3), during the first surface treatment, the concentration of the polyacid solution used is 5 to 15 mg / ml; In step 4), during the second surface treatment, the concentration of the polyacid solution used is 0.2-1 mg / ml.

2. The method for preparing a transparent electrode based on polyacid treatment according to claim 1, characterized in that: In step 1), the concentration of the polyacid solution stock solution is 0.2-15 mg / ml.

3. The method for preparing a transparent electrode based on polyacid treatment according to claim 1, characterized in that: In step 2), the thickness of the PEDOT:PSS film is 30 to 150 nm.

4. The method for preparing a transparent electrode based on polyacid treatment according to claim 1, characterized in that: In step 3), the reaction conditions of the first surface treatment are: soaking at room temperature for 10 to 60 minutes; In step 4), during the second surface treatment, the polyacid solution is dripped until it covers the surface of the film.

5. The method for preparing a transparent electrode based on polyacid treatment according to claim 1, characterized in that: In step 3), the specific operation of cleaning is: immersing the PEDOT:PSS film in a methanol or ethanol solution for rinsing for 1 to 3 minutes and then taking it out; The specific operation of annealing is: annealing the rinsed PEDOT:PSS film at 100-150° C. for 10-60 minutes.

6. The method for preparing a transparent electrode based on polyacid treatment according to claim 1, characterized in that: In step 2), the solution film is formed by spin coating, wire rod coating, slot extrusion coating or printing; In step 4), the excess polyacid solution is removed, specifically by spin coating, doctor blade coating or slit coating.

7. A transparent electrode based on polyacid treatment obtained by the method for preparing a transparent electrode based on polyacid treatment according to any one of claims 1 to 6, characterized in that: The thickness of the transparent electrode based on polyacid treatment is 30 to 150 nm.

8. An application of the polyacid-treated transparent electrode according to claim 7 in the preparation of a perovskite solar cell, wherein the structure of the perovskite solar cell comprises, from bottom to top, a transparent electrode layer (1), a hole transport layer (2), a perovskite active layer (3), an electron transport layer (4) and a metal electrode layer (5), characterized in that: The polyacid-treated transparent electrode is used as a transparent electrode layer (1) and / or a hole transport layer (2).